The crackling sound of Leidenfrost stars. (2nd July 2018) - Brunet, P.
Abstract : Liquid drops deposited on a hot plate can experience a boiling crisis, when the vapour flux is strong enough to ensure the levitation of the drop and the relative insulation of the liquid from the solid. It is often denoted Leidenfrost effect, after the German Johann Gottlob Leidenfrost, who first reported it in 1756. While many studies have encompassed various applied issues associated with this phenomenon, aiming to control and prevent its appearance, Ma & Burton ( J. Fluid Mech., vol. 846, 2018, pp. 263–291) focused on the spontaneous appearance of a standing wave at the free surface, together with temporal oscillations, making the drop adopt the shape of a star. Their far-reaching study presents exhaustive results using six different liquids with a range of different volumes and temperatures, in which they systematically extracted the drop dynamics together with the pressure fluctuations in the vapour cushion below.